2022
DOI: 10.1021/acs.nanolett.2c01524
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Derived Anion-Anchoring Nano-CaCO3Coating for Regulating Ion Transport on Li Metal Surface

Abstract: The free transport of anions in a Li metal battery can cause multiple issues, including a high anion transference number, space charge, and concentration polarization, eventually leading to uncontrolled dendrite formation and decreased performance. Herein, we report an anion-anchoring nano-CaCO 3 (NC) coating derived from eggshell biowaste for stabilizing Li metal anodes. As the adsorption of local TFSI − anions onto the NC adsorbent can undermine the anion concentration gradient and promote rapid Li-ion diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…On the contrary, the electrolyte droplets quickly diffuse to the surface of HNTs and HNTs/Ag (almost 0° after 0.5 s), showing good affinity between the electrolyte and HNTs or HNTs/Ag, which is expected to lower the charge-transfer resistance, increase the electrolyte absorption, and provide a uniform electrolyte and sodium ion distribution . The strong wettability of HNTs and HNTs/Ag with the electrolyte may be related to the strong adsorption caused by the porous structure and polar groups of HNTs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the electrolyte droplets quickly diffuse to the surface of HNTs and HNTs/Ag (almost 0° after 0.5 s), showing good affinity between the electrolyte and HNTs or HNTs/Ag, which is expected to lower the charge-transfer resistance, increase the electrolyte absorption, and provide a uniform electrolyte and sodium ion distribution . The strong wettability of HNTs and HNTs/Ag with the electrolyte may be related to the strong adsorption caused by the porous structure and polar groups of HNTs …”
Section: Resultsmentioning
confidence: 99%
“…According to Sand’s equation, the time for dendrites to start growing will be effectively prolonged by reducing the current density J and anion migration number t a . At present, electrolyte additives, protective layers, and a composite separator with anionic fixation function are used to retard the diffusion of anions or completely immobilize them. Extensive research has shown that collector modification, artificial solid electrolyte interphase (SEI) construction, and scaffolds design with sodiophilic site can effectively avoid excessive local current.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the advantages of batteries, various performance indicators, which include the production cost, energy storage capacity density, rate performance, lifetime, and cyclic stability, are used [ 4 , 5 , 6 ]. The electrochemical properties of Li-ion batteries depend on the electrode materials which play a major role as a key component [ 7 , 8 , 9 , 10 , 11 ]. Thus, developing a suitable and high-performance electrode material is of special significance.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium (Li) metal has been pursued as the “Holy Grail” of anode materials for Li-based secondary batteries because of its high specific capacity and the lowest redox potential. In general, during battery operations, a solid electrolyte interphase (SEI) film will be spontaneously generated on the surface of the Li metal anode due to the parasitic reactions between highly reactive Li and the electrolyte, protectively passivating the anode. However, the SEI film formed in most electrolyte systems is unstable and suffers from repeated breakage/repair due to the volume change upon cycling. , This will lower the Coulombic efficiency (CE) by continuously consuming the active Li sources and electrolytes as well as trigger safety issues because of dendritic Li growth, severely limiting the application of Li metal anodes. , Therefore, constructing a robust artificial SEI film to improve the cyclability of Li metal anodes in practical Li metal batteries (LMBs) is of great importance. …”
mentioning
confidence: 99%
“…7,8 This will lower the Coulombic efficiency (CE) by continuously consuming the active Li sources and electrolytes as well as trigger safety issues because of dendritic Li growth, severely limiting the application of Li metal anodes. 9,10 Therefore, constructing a robust artificial SEI film to improve the cyclability of Li metal anodes in practical Li metal batteries (LMBs) is of great importance. 11−13 Lithium fluoride (LiF) with a low surface diffusion barrier and high surface energy facilitates fast Li ion diffusion and inhibits interfacial side reactions; thus, it is regarded as a preferred SEI component and enables superior battery performance.…”
mentioning
confidence: 99%